The Main Directions of Modern Research in Department of Landscape Science of Institute of Geography of the National Academy of Sciences of Ukraine - Chekhniy, V. M.; Sorokina, L. Yu.; Sorokina, L. Yu.; Tymuliak, L. M.; Farion, Yu. M. (Ukrainian Geographical Journal, 2024)
The purpose of the publication is to reveal the content of modern developments of the Department of Landscape Science in the context of the previous research achievements of the scientific unit. The central part of them is presented within four complementary research areas: geoinformation mapping of landscapes, study of anthropogenic changes in landscapes, landscape planning and nature conservation, and landscape science. The main results of the work in the first of these areas include the creation of a prototype GIS of a landscape map of Ukraine at a base scale of 1:500,000, as well as cartographic support for most of the department’s other activities. The research on anthropogenic landscapes is primarily concerned with the study of the current state and evolution of radioactively contaminated landscapes of the Chornobyl Exclusion Zone; detection of land cover changes using remote sensing data; generalizing works on the methodology of integrated studies of anthropogenic landscapes and a unified classification of natural and anthropogenically modified landscape complexes. Landscape planning is a new research area based on European, in particular German, experience. For 15 years, the Institute of Geography of the National Academy of Sciences of Ukraine, with the participation of the department’s staff, has been adapting it to the conditions of Ukraine by the example of the Cherkasy region. This led to the introduction of the landscape-planning tool into the regulatory framework for spatial planning and to its broader application in other areas of Ukraine. The department’s studies in the field of nature conservation landscape science covered both theoretical and methodological issues (in particular, substantiating the formation of Ukraine’s econetwork and determining approaches to expanding the network of protected areas) and the solution of several practical problems related to many protected areas and objects in different regions of Ukraine. With the outbreak of the full-scale war in Ukraine, the primary focus of the department’s activities shifted to researching the impact of the war on the landscapes of Ukraine and substantiating the best ways to preserve and restore them.